The effect of using stations of varying levels in learning some motor skills Five-a-side football (Journal of the College of Basic Education, 2022)
Teaching motor skills by following stations of different levels gives flexibility in selecting the content, as it activates all learners to perform a variety of actions. As for the time of the content and the special arrangements in each station, it can be decided by the teacher or the student, and the environment must be arranged in order to perform at the same time more than one work in one lesson. Hence the importance of the research in order to find out the effect of using stations of different levels in learning some non-motor skills in five-a-side football.